Driving the quadricyclane-to-norbornadiene isomerization by charge separation with perylenediimide as electron acceptor - Zika, Wiebke; Leng, Andreas; Weiß, René; Pinter, Simone; Schüßlbauer, Christoph; Clark, Timothy; Hirsch, Andreas; Guldi, Dirk Michael (Chemical Science, 2023)
Through comprehensive photo-assays, this study investigates the reaction coordinate governing the interconversion between quadricyclane (QC) and norbornadiene (NBD) upon photo-irradiation up to a wavelength of 550 nm. To harness this spectroscopic range for energy release, we link the NBD-core with a highly electron-accepting perylenediimide (PDI) with broad absorption, achieving strong electronic coupling between them. We detail the successful synthesis and present extensive DFT calculations to determine the amount of stored energy. By means of transient absorption spectroscopy, an oxidative electron transfer is observed during the QC-to-NBD isomerization following the initial PDI photoexcitation. This charge-separated state is key to triggering the back-isomerization with visible light excitation.
CRIS-Team Scopus Importer:2023-10-20

Intramolecular Singlet Fission in Individual Graphene Nanoribbons─Competition with a Charge Transfer - Greißel, Phillip; Beneventi, Giovanni Mariano; Weiß, René; Wollny, Anna-Sophie; Dubey, Rajeev K.; Melle-Franco, Manuel; Clark, Timothy; Mateo-Alonso, Aurelio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2025)
Graphene nanoribbons (NRs) constitute a versatile platform for developing novel materials, where their structure governs their optical, electronic, and magnetic properties while also shaping their excited-state dynamics. Here, we investigate a set of three twisted N-doped molecular NRs of increasing length, obtained by linearly fusing perylene diimide to pyrene and pyrazino- or thiadiazolo-quinoxaline residues. By employing various temperature-dependent time-resolved spectroscopy techniques, we reveal how the flexible twisted NR geometry promotes the formation of a mixed electronic state with varying contributions from locally excited and charge-transfer (CT) states. The fate of this mixed state is highly sensitive to the molecular geometry, length, and solvent polarity. For the shortest NR, intersystem crossing dominates the deactivation pathway, efficiently generating triplets in low-polarity solvents. In contrast, for the extended NRs, intramolecular singlet fission (SF) takes place within a single nanoribbon. This is enabled by enhanced superexchange coupling due to a pronounced push-pull nature and the existence of multiple localized π-electron states caused by heteroatom doping, thereby circumventing the need for dimeric interactions typically associated with conventional SF systems. In higher-polarity environments, evidence of a (diabatic) CT state emerges. These findings underscore the intricate relationship between geometry, energy levels, and excited-state dynamics in twisted N-doped NRs.
CRIS-Team Scopus Importer:2025-04-01

Molecular Acenes for Light Capture, Conversion, and Storage - Greißel, Phillip; Wollny, Anna-Sophie; Bo, Yifan; Thiel, Dominik; Weiß, René; Guldi, Dirk Michael (Accounts of Materials Research, 2024)
Conspectus Efficient photovoltaics (PV) require capturing and converting solar energy across a broad range of energy. Losses due to thermalization and sub-bandgap photons place, however, significant boundaries on the performance of solar cells. For conventional single-junction cells, the theoretical maximum power conversion efficiency is capped at 33%, a constraint known as the detailed balance limit. Realizing the full potential of PVs requires developing novel strategies to overcome this fundamental obstacle. This Account describes the photon-management capabilities of acenes and addresses these fundamental losses en-route toward enhancing PV performances. For high-energy photons that exceed the semiconductor’s bandgap energy, singlet fission (SF) is a down-conversion pathway to mitigate thermalization losses. SF is a process in organic materials, in which a singlet excited state is split into two independent triplet excited states, effectively doubling the number of charge carriers. Pentacenes stand out among acenes due to their exergonic nature of SF. Numerous molecular pentacene dimers have been synthesized to elucidate the relationship between structure and enhancing SF efficiency. A broader light-harvesting range of SF materials is realized by covalently attaching complementary absorbing energy donors to set up energy donor-acceptor conjugates. Förster resonance energy transfer (FRET) is operative in these energy donor-acceptor conjugates, effectively extending the absorption of SF materials, as the energy donor efficiently transfers its absorbed excitation energy to the energy acceptor. Our studies on various binding motifs show that FRET efficiency depends not only on parameters like the energy donor-acceptor distance and spectral overlap but also on subtle factors such as the alignment of transition dipoles, which significantly affect the energy transfer dynamics and efficiency. Turning to low-energy photons, triplet-triplet annihilation up-conversion (TTA-UC) provides a means of light up-conversion and, thereby, the reduction of sub-bandgap losses. In TTA-UC, a singlet excited state that is potent enough to generate charge carriers is formed by combining two triplet excitons. It is effectively the reverse process of SF. The higher triplet energy of tetracene and an endergonic SF renders them highly effective for TTA-UC. We focus on various tetracene-based systems that maximize TTA-UC efficiency. Besides TTA-UC, two-photon absorption (TPA) is yet another mechanism to leverage below-bandgap photons. It is a nonlinear optical (NLO) process, and acenes reveal NLO properties that are essential for extending light absorption into the near-infrared and still powering SF. We demonstrate in our proof-of-concept studies how TPA further broadens the application potential of acenes for PV systems. The strategies outlined in this Account illustrate that acenes are valuable for addressing mechanistic losses in conventional solar cells. In the final section, we examine light storage following SF by means of interfacial electron transfer. Efficient charge-injection powered by SF materials still requires more research before being implemented in large-scale PV designs. Overall, the advances discussed in this Account not only highlight the pivotal role of acenes as model systems to investigate photon down- and up-conversion processes but also paint a promising picture that more efficient solar energy conversion schemes exceeding the detailed-balance limit can be realized by implementing these materials.
CRIS-Team Scopus Importer:2025-02-04

Tetracene Dimers: A Platform for Intramolecular Down- and Up-conversion - Bo, Yifan; Hou, Yuxuan; Thiel, Dominik; Weiß, René; Clark, Timothy; Ferguson, Michael J.; Tykwinski, Rik R.; Guldi, Dirk Michael (Journal of the American Chemical Society, 2023)
Photon energy conversion can be accomplished in many different ways, including the two opposing manners, down-conversion (i.e., singlet fission, SF) and up-conversion (i.e., triplet-triplet annihilation up-conversion, TTA-UC). Both processes have the potential to help overcome the detailed balance limit of single-junction solar cells. Tetracene, in which the energies of the lowest singlet excited state and twice the triplet excited state are comparable, exhibits both down- and up-conversion. Here, we have designed meta-diethynylphenylene- and 1,3-diethynyladamantyl-linked tetracene dimers, which feature different electronic coupling, to characterize the interplay between intramolecular SF (intra-SF) and intramolecular TTA-UC (intra-TTA-UC) via steady-state and time-resolved absorption and fluorescence spectroscopy. Furthermore, we have used Pd-phthalocyanine as a sensitizer to enable intra-TTA-UC in the two dimers via indirect photoexcitation in the near-infrared part of the solar spectrum. The work is rounded off by temperature-dependent measurements, which outline key aspects of how thermal effects impact intra-SF and intra-TTA-UC in different dimers.
CRIS-Team Scopus Importer:2023-10-06

Tuning Interactions to Control Molecular Down Conversion in [2.2]Paracyclophane Bridged Oligo-Tetracenes - Rapp, Mario R.; Weiß, René; Wollny, Anna-Sophie; Guldi, Dirk Michael; Bettinger, Holger F. (Advanced Functional Materials, 2024)
In tetracene, the energies of the lowest singlet excited state and twice that of the lowest triplet excited state are similar, allowing both down-conversion (i.e., singlet fission, SF) and up-conversion (i.e., triplet-triplet annihilation up-conversion, TTA-UC) processes. Through-space and through-bond contributions to the inter-tetracene coupling in purposefully designed oligomers play a crucial role in determining which of the two processes dominates. In this work, the focus is exclusively on SF in newly synthesized oligo-tetracenes linked by conjugated [2.2]paracyclophane (PCP) building blocks. By choosing different PCP substitution patterns and by varying the degree of substitution the inter-tetracene couplings are addressed. An independent variable is connecting the tetracences to the PCP at different positions to alter the through-bond and through-space coupling of the resulting oligo-tetracenes. The novel oligo-tetracenes are investigated by means of steady-state and time-resolved absorption and fluorescence spectroscopies with respect to the initial events of SF, that is, the transformation of a singlet excited state into a correlated triplet pair state. Briefly, through-space couplings are profoundly weaker than through-bond couplings that enable the correlated triplet pair state formation. If interactions are through-space, correlated triplet pair state formation is turned off, while it is turned on if through-bond interactions are operative.
CRIS-Team Scopus Importer:2024-03-15
Keywords: acenes; cyclophanes; excited states; oligomers; photophysics; singlet fission